Etika Konsumsi dan Krisis Sampah Plastik: Analisis Tafsir Tematik-Kontekstual dalam Tafsīr al-Marāgī - Abdurrohim; Yanyan Nurdin; Parhan Mubarok; Risdi Darussalam (Lembaga Penelitian, Penerbitan dan Pengabdian kepada Masyarakat (LP3M) IAIFA Kediri, 2026)
The plastic waste crisis in Indonesia has reached a critical level, driven largely by unsustainable consumption patterns that contribute to environmental degradation. This study aims to examine Qur’anic consumption ethics through the perspective of Tafsīr al-Marāgī and to contextualize them within the contemporary plastic waste crisis. The novelty of this study lies in integrating thematic exegesis with a contextual-ecological approach to interpret verses on isrāf (excess), fasād (corruption), and tabdhīr (wastefulness) as a critique of modern consumption practices, particularly the use of single-use plastics. This study employs a qualitative library-based method using a thematic exegesis approach. The primary data source is Tafsīr al-Marāgī, supported by exegetical literature, books, and relevant scholarly articles. The analysis is conducted through linguistic examination of the verses, interpretation based on al-Marāgī, and contextualization in relation to contemporary environmental issues. The findings indicate that the prohibition of isrāf emphasizes the importance of limiting consumption in alignment with environmental sustainability. The concept of fasād highlights the causal relationship between human behavior and ecological damage, while the widespread use of single-use plastics reflects a form of tabdhīr, indicating the inefficient and irresponsible use of resources. This finding suggests that Qur’anic consumption ethics remain highly relevant in promoting environmental awareness and supporting the sustainability of human life in today’s context.